Studi deskriptif karakteristik masalah peserta badan penyelenggara jaminan sosial kesehatan di Poli Gigi Klinik Karya Prima selama bulan Januari-Juli 2016 - Mia Ayustina Prasetya (Bali Dental Journal, 2019)
Introduction: Health insurance is insurance that covers the whole or a part of the risk of a person incurring medical expenses, spreading the risk over a large number of persons. Klinik Karya Prima is one of the 24 hour medical clinic in Denpasar which provides health care for 18.000 insurers of Badan Penyelenggaran Jaminan Sosial Kesehatan (BPJS). The aim of this study is to describe about oral health problems of the BPJS insurers whose came to Dental Department of Klinik Karya Prima from January to June 2016. Method: This study is a descriptive study and was conducted on 2828 patients. All data grouping variable were based on age, gender, diagnosis, and dental treatment.Result: The result shows that most of the patients were women (53.3%), the most diagnosis was pulp necrosis (42.3%), and it leads to the most dental treatment which was mummification (22.6%). Conclusion: The conclusion of this study is that the caries incidence in our community especially the BPJS insurers at Dental Department of Karya Prima Dental Clinic is pretty high and those people might not consider it as a priority since the Pulp Necrosis diagnosis was often reported.